Kindergarten teachers’ facilitation of social and emotional learning in classroom play contexts - Nicole Larsen; Angela Pyle; Erica Danniels; Marsha Marzouca; Raadiyah Nazeem (Education Inquiry)
Play occupies a critical role in the kindergarten classroom, and the expansion of formal play-based learning programmes have brought connections between play and learning to the forefront. With respect to social and emotional learning (SEL), child-directed play has been viewed as critical, while teacher direction has been framed as a potential disruption to this learning. However, teachers facilitate different types of play in kindergarten with varying degrees of assistance, yet few studies have looked at the ways teachers target children’s SEL across different play configurations. The current study gathered observational data in 20 play-based kindergarten classrooms. Video data were coded according to the type of play (child-directed or teacher-facilitated), SEL competency, and type of teacher promotion. Across both types of play, teachers focused primarily on supporting children’s relationship skills and self-management skills in an incidental way, while other competencies not practiced spontaneously in play largely went overlooked. Skills were targeted most often during teacher-facilitated play, underscoring the importance of this context for children’s SEL. Overall, these findings illustrate positive examples of teacher promotion of SEL in play, while underscoring the need for more intentional targeting of broader competencies to promote all areas of children’s SEL in a developmentally appropriate manner.